(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
The guarantee of a trial within a reasonable time is a special element in the content of the right to a fair trial (articulated in Article 6 of the Convention for the Protection of Human Rights and Fundamental Freedoms). This guarantee is transformed into a right to a trial within a reasonable time which belongs to the parties and other participants in the civil proceedings due to the obligation on member States to organize their judicial systems in such a way that their courts are able to guarantee everyone’s right to a final decision on disputes concerning civil rights and obligations within a reasonable time. The Republic of North Macedonia, ratifying the Convention for the Protection of Human Rights and Fundamental Freedoms, operationalized the duty to organize the judicial mechanism by enabling the courts to make decisions within a reasonable time, in a way that the Law on Courts gives jurisdiction to the Supreme Court of the Republic of North Macedonia to decide at the request of the parties and other participants in the proceedings for violation of the right to a trial within a reasonable time in civil proceedings starting from the case law of the European Court for protection of human rights and fundamental freedoms. Exactly because of this subject of analysis of this paper are the criteria for assessment of violation of the right to a trial within a reasonable time established through the case law of the European Court of Human Rights and Fundamental Freedoms and their implementation in the case law of the Supreme Court of North Macedonia. These are casually created criteria that refer to: 1) the complexity of the case 2) the conduct of the court or other body of public conduct and 3) the conduct of the parties, especially the applicant, during and the duration of the procedure.